2006
DOI: 10.1158/0008-5472.can-06-0974
|View full text |Cite
|
Sign up to set email alerts
|

Notch1-Induced Transformation of RKE-1 Cells Requires Up-regulation of Cyclin D1

Abstract: RKE-1 cells induced to overexpress activated Notch1 (RKE-ER-N ic

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 54 publications
5
33
0
1
Order By: Relevance
“…Their early expansion correlates closely with later tumor formation, and abrogation of this early expansion in cyclin D1-deficient mice also correlates with the absence of tumors in these KO mice. This latter result extends a previous report showing that in vitro transformation of RKE-1 cells by N1 IC requires cyclin D1 (Stahl et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Their early expansion correlates closely with later tumor formation, and abrogation of this early expansion in cyclin D1-deficient mice also correlates with the absence of tumors in these KO mice. This latter result extends a previous report showing that in vitro transformation of RKE-1 cells by N1 IC requires cyclin D1 (Stahl et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Our in vitro findings showed that Notch expression was associated with TEC proliferation and cyclin D1 expression (as also described in other cells; ref. 37). Coculturing Jag1expressing stromal cells with TECs or fibroblasts was also sufficient to induce expression of cyclin D1, both in epithelial cells and in fibroblasts (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…Cyclin D1 expression during development was shown to correlate with the expression of Notch, and cyclin D1 was required for Notch1-mediated transformation and contact-independent growth. 89 Subsequent studies in breast cancer cells demonstrated that cyclin D1 enhances Notch1 activity by inhibiting the expression of its negative regulator, Numb. 90 Consistent with these findings, cyclin D1 knockout mice showed resistance to Notch1-induced mammary tumorigenesis.…”
Section: Micrornasmentioning
confidence: 99%